2013
DOI: 10.1007/s00449-013-0936-0
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acid production by marine bacteria

Abstract: Polyunsaturated fatty acids are important in maintaining human health. Limitations associated with current sources of ω-3 fatty acids and ω-6 fatty acids, from animal and plant sources, have led to increased interest in microbial production. Marine bacteria may provide a suitable alternative, although the isolation of production strains and the identification of operating conditions must be addressed before manufacturing processes become economically viable. Marine isolate 560 was identified as an eicosapentae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 24 publications
0
22
1
Order By: Relevance
“…However, we have been successful in isolating PUFA producers from the Arabian Sea along the Indian western coast; falling in the tropical belt generally having ambient temperatures around the year. This information goes contrary to the common notion that only psychrophilic and halotolerant microorganisms from the colder regions of the world are able to produce PUFA 2,5,19 .…”
Section: Gc/mscontrasting
confidence: 78%
See 4 more Smart Citations
“…However, we have been successful in isolating PUFA producers from the Arabian Sea along the Indian western coast; falling in the tropical belt generally having ambient temperatures around the year. This information goes contrary to the common notion that only psychrophilic and halotolerant microorganisms from the colder regions of the world are able to produce PUFA 2,5,19 .…”
Section: Gc/mscontrasting
confidence: 78%
“…Since then, it has been confirmed that PUFA production occurs in numerous bacterial species isolated from Antarctic regions as well as temperate marine environments. Attention of many researchers has thus been centered on cold seas and deep oceans 2,5,8,19 . However, we have been successful in isolating PUFA producers from the Arabian Sea along the Indian western coast; falling in the tropical belt generally having ambient temperatures around the year.…”
Section: Gc/msmentioning
confidence: 99%
See 3 more Smart Citations